IMOBILISASI ASAM HUMAT PADA KITOSAN MENGGUNAKAN METODE PENGIKAT-SILANG TERPROTEKSI DAN APLIKASINYA SEBAGAI ADSORBEN Cd(II) DAN Hg(II) - , YEYEN ARIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Immobilization of humic acid on chitosan using protected cross-linking method and its application as adsorbent of Cd(II) and Hg(II) ion has been done. This research was initiated with isolation of humic acid and chitin deacetylation. Immobilization was done by interacting humic acid with Cd(II) ion before crosslinking on chitosan using glutaraldehyde as cross-linking agent. After crosslinking, Cd(II) ion is deprotected using EDTA solution. Resulted adsorbent is characterized using infrared spectrophotometer and used to adsorp Cd(II) ion by analyzing effect of pH, rate and adsorption equilibrium constant, identification of functional group that plays its role in adsorption, and effect of other ion metal specially Hg(II) toward adsorption. The isolated humic acid has ash content of 0.73% and chitosan has deacetylation degree of 74.21% for base line (a) method and 82.88% for base line (b) method. The result showed that adsorption of Cd(II) ion by adsorbent is optimum at pH 6. The adsorption of Cd(II) ion by the adsorbent follows the pseudo second order kinetic model of Ho with adsorption rate constant of 0.2034 g/mg minute. Functional groups contained in adsorbent that plays its role in adsorption of Cd(II) ion are âCOOH and âOH group. Forming Cd(II) ion template at humic acid active site protection is not effective to enhance selectivity of resulted adsorbent toward Cd(II) ion at the presence of Hg(II) ion. Keywords: humic acid, chitosan, immobilization, cross-linking, adsorption